2023
DOI: 10.1039/d3dt00511a
|View full text |Cite
|
Sign up to set email alerts
|

The π-interactions of ammonia ligands evaluated byab initioligand field theory

Abstract: Ammonia and amine ligands are commonly assumed to be σ-only ligands in coordination chemistry, i.e. they are not expected to interact significantly with a metal via a π-path. Ligand field...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…There are many examples for which the combination of LFT, AOM and computational chemistry work in a clear and unambiguous way. As we showed in previous publications, 21,25…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…There are many examples for which the combination of LFT, AOM and computational chemistry work in a clear and unambiguous way. As we showed in previous publications, 21,25…”
Section: Discussionsupporting
confidence: 64%
“…With the above examples and the ones in previous publications 21,25 it is shown that our procedure can be applied to a variety of transition metal complexes. Nonetheless, the user must be careful and aware of problems and ambiguities in the AOM parameterization choices that might not be obvious.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations